2015
DOI: 10.1056/nejmoa1509773
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of Sexual Transmission of Ebola Virus

Abstract: Summary A suspected case of sexual transmission from a male survivor of Ebola virus disease (EVD) to his female partner (the patient in this report) occurred in Liberia in March 2015. Ebola virus (EBOV) genomes assembled from blood samples from the patient and a semen sample from the survivor were consistent with direct transmission. The genomes shared three substitutions that were absent from all other Western African EBOV sequences and that were distinct from the last documented transmission chain in Liberia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
336
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(350 citation statements)
references
References 17 publications
7
336
0
1
Order By: Relevance
“…In rare cases, encephalitis has also been noted [30][31][32][33] . Filoviruses have also been detected by PCR and/or virus isolation in the breast milk 34,35 and semen [36][37][38][39] of survivors. The persistence of filoviruses in semen is particularly concerning, with detection in one individual occurring 565 days after discharge from an EBOV treatment centre in Liberia 38 .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…In rare cases, encephalitis has also been noted [30][31][32][33] . Filoviruses have also been detected by PCR and/or virus isolation in the breast milk 34,35 and semen [36][37][38][39] of survivors. The persistence of filoviruses in semen is particularly concerning, with detection in one individual occurring 565 days after discharge from an EBOV treatment centre in Liberia 38 .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Sensory examination cannot be performed symptoms, although at decreasing rates over time (with all survivors who were tested at 2-3 months after onset having EBOV RNA-positive semen, 65% of survivors positive at 4-6 months after onset, and 26% positive at 7-9 months after onset) [42]. These findings are of further interest given the potential for sexual transmission of EVD, as in the previously mentioned March 2015 case in Liberia [15]. Owing to risk of sexual transmission during convalescence, Ebola survivors are now recommended to practice safe sex with barrier protection for at least 12 months after recovery from EVD [43].…”
Section: Viral Persistencementioning
confidence: 87%
“…Although seemingly rare, Ebola can also be transmitted through sexual contact, even in the convalescent phase, as Ebola virus can persist in semen for months after recovery from the illness [14]. A case of Ebola occurred in a woman in March 2015 whose only known Ebola contact was via unprotected sex with an EVD survivor; after genetic analysis it was confirmed that survivor's and the patient's Ebola virus genomes were identical and that the transmission likely occurred from sexual contact [15]. Butchering and handling of bushmeat, including nonhuman primates and bats, have also previously been associated with outbreaks of Ebola [16].…”
Section: Clinical Properties Transmissionmentioning
confidence: 99%
“…Variability in lethality might also relate to factors such as time from disease onset to presentation for care, quality of care available, patient demographics, or variant of infecting virus. 14,[22][23][24] Accurate viral load measurement is also important in interpreting Ebola virus persistence in and transmission risk from immuneprivileged body compartments and fl uids, 25 including the male gonads or semen, [25][26][27][28] eyes, 29 CNS, 30 breast milk, 31 and the intrauterine space in pregnant women. 32 Additionally, Ebola virus has occasionally been found in sweat and urine, 33 and in atypical or asymptomatic cases.…”
Section: Importance Of Fi Lovirus Load Determinationmentioning
confidence: 99%